Advanced Bioelectrical Signal Processing Methods: Past, Present, and Future Approach-Part III: Other Biosignals - Martinek, Radek; Ladrova, Martina; Sidikova, Michaela; Jaros, Rene; Behbehani, Khosrow; Kahankova, Radana; Kawala-Sterniuk, Aleksandra (Sensors (Basel, Switzerland), 2021)
Analysis of biomedical signals is a very challenging task involving implementation of various advanced signal processing methods. This area is rapidly developing. This paper is a Part III paper, where the most popular and efficient digital signal processing methods are presented. This paper covers the following bioelectrical signals and their processing methods: electromyography (EMG), electroneurography (ENG), electrogastrography (EGG), electrooculography (EOG), electroretinography (ERG), and electrohysterography (EHG).
Keywords: electrooculography; electrohysterography; elektroretinografie; electroretinography; elektrookulografie; electrogastrography; Electroretinography; elektromyografie; electroneurography; Electrooculography; biomedical signals; počítačové zpracování signálu; electromyography; signal processing; Electromyography; Signal Processing, Computer-Assisted